Teaching Strategy of Chemistry Concepts Based on Deep Learning - Yang, Xinling (Advances in Social Sciences Research Journal, 2023)
Deep learning is a meaningful learning process in which students are fully engaged, successful, and developed around challenging learning topics. Based on deep learning, this paper discusses the teaching strategies of chemical concepts such as summary, analogy, deductive reasoning, and multiple representations, as well as the application cases of strategy implementation, and introduces in detail the application of multiple representation strategies and the requirements of each representation method.